Financial inclusion and bank risk-taking: the effect of information sharing - Marcelin, I.; Sun, W.; Teclezion, M.; Junarsin, Eddy (Elsevier, 2022)
We explore how information-sharing and financial inclusion influence bank risk in 84 countries from 1996 to 2020. Results show that greater information-sharing and financial inclusion lessen bank risk levels. The average bank’s Z-score increases by 3.51–9.09%, attributable to enhanced information-sharing and higher financial inclusion. Inclusion-based deposit mobilization reduces bank probability of insolvency, suggesting that inclusion provides banks with cheap funding sources, reducing moral hazard problems and risky behaviors. Results remain robust across risk indicators and controlling for FinTech-based inclusion and COVID-19-induced risk. They support the hypothesis of increased social returns to transparency, information-sharing, and reaching out to financially excluded segments.